2018
DOI: 10.1002/jmor.20835
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of reproductive accessory glands in female Sepia pharaonis (Cephalopoda: Sepiidae) sheds light on egg encapsulation

Abstract: The pharaoh cuttlefish, Sepia pharaonis, is an important cephalopod fishery species in southeastern Asia, with understudied reproductive physiology. The present study aimed to investigate the cellular characteristics of epithelial cells found in the nidamental glands (NGs) and accessory NGs (ANGs), as well as the structural connections between these two glands in mature female S. pharaonis. A histological analysis revealed two types of epithelial cells in NGs: Alcian blue‐positive, PAS‐negative mucosubstance‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The epithelial cells of the lumen of the accessory nidamental gland in S. pharaonis showed the uneven distribution of cilium. This was similar to the morphology described in the studies of Nair et al (2005) and Huang et al (2018) on the accessory nidamental gland. In addition, studies have found that the cephalopod accessory nidamental gland contains symbiotic bacteria.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The epithelial cells of the lumen of the accessory nidamental gland in S. pharaonis showed the uneven distribution of cilium. This was similar to the morphology described in the studies of Nair et al (2005) and Huang et al (2018) on the accessory nidamental gland. In addition, studies have found that the cephalopod accessory nidamental gland contains symbiotic bacteria.…”
Section: Discussionsupporting
confidence: 91%
“…Based on criteria used in fish descriptions, ovarian development and oogenesis have been characterized in a few cephalopod species, including Loligo vulgaris L amarck 1798 (Melo & Sauer, 1998), Octopus vulgaris C uvier 1797 (Di Cosmo et al, 2001), Octopus maya Voss & Solís 1966 (Avila‐Poveda et al, 2009), Amphioctopus fangsiao ( d'Orbigny [in A. Férussac & d'Orbigny], 1839–1841) (= Octopus ocellatus ) (Wang et al, 2015), Sepiella inermis (= maindroni ) ( Van Hasselt [in Férussac & d'Orbigny ] 1835) (Jiang et al, 2007), and Sepia esculenta H oyle 1885 (Yin et al, 2018). However, in S. pharaonis , the structure of the accessory nidamental gland is the only aspect of the reproductive system to have been studied (Huang et al, 2018; Nair et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial activity is found in extracts of the ANG in squid 4,5 and cuttlefish 6 , which is interesting in light of the highly similar bacterial composition of the egg jelly coat and ANG in these cephalopods 7,8 . The ANG may play an important role in bacterial delivery from the parent to the egg capsule by preventing contamination from microorganisms in the benthic environment 9 . In squid and cuttlefish, at least some symbiotic bacteria are delivered from the marine environment and selected by the host 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study further suggested that the environment affects the microbial compositions of individuals, whereas maturity levels exert progressive effects on microbial dynamics over time (Yang et al, 2021). These host-selected bacteria are transmitted to the egg jelly coat in some squid and cuttlefish (Kerwin and Nyholm, 2017;Huang et al, 2018). Suppression of the bacteria deposited on the eggs by antibiotic treatment led to susceptibility to heavy biofouling and very low hatching rates compared with untreated eggs in Hawaiian bobtail squid (Kerwin et al, 2019).…”
Section: Control Of Mutualistic Microbiota In Squid By Innate Immunitymentioning
confidence: 86%